FRI0483 Work capacity and quality of life in a cohort of patients with early psoriatic arthritis in argentina. (15th June 2017) - Colombres, F; Berman, H; Spindler, A; Spindler, W; Cocco, JA Maldonado; Orozco, MC; Schneeberger, E; Ortiz, A; Paira, S; Zalazar, M; Rillo, O; Baenas, D; et al.
Abstract : Objectives: To evaluate work capacity and quality of life in patients with early Psoriatic Arthritis (PsA). Methods: Multi-center study in which patients with recent onset of PsA (disease duration <3 years) who met the CASPAR criteria established by the Early Spondyloarthritis Committee (CONEART) were enrolled. Work loss and lost workdays within six months prior to the baseline visit attributable to their baseline condition were evaluated, as well as quality of life, measured by PsAQol. Statistical analysis: descriptive statistics, Spearman's correlation, multiple linear regression model. Results: 108 patients with a PsA diagnosis were enrolled. 53% (57/108) were male, of a mean age of 48.4 (SD 12.5). The mean PsA disease duration was 17.6 (SD 9.8) months. 4/60 patients (6.6%) were positive for HLA- B27 . BASDAI 4.81±2.66; BASFI 3.75±2.70; PsAQoL 7.24±6.44; HAQ-A 0.72±0.61, physician global activity assessment (by Visual Numeric Scale, VNS) 3.76±2.33, and pain assessment (VNS) 5.22±2.98. The average days lost due to the condition within the past 6 months was 8.6 (SD 32.1), it was significantly associated with the presence of enthesitis, number of swollen joints, worse BASDAI, BASFI, lower level of education, and higher pain and physician global activity assessment (p<0.0001). Five patients lost their job due to PsA. 12% of the patients had a disability certificate and the possession of one, according to the logistic regression model, was associated with a longer PsA disease duration (OR 1.09, p=0.02). A poorer quality of life was significantly correlated to the physician assessment of disease activity (p<0.001) and pain (p<0.01) using a linear regression model. Conclusions: In this cohort of patients with early PsA, the deterioration of work capacity expressed in lost workdays was associated with disease activity parameters and functional disability. The physician global activity assessment and pain were the main factors associated with the impact on patient's quality of life. Having a disability certificate was associated with longer disease duration. Although this is an early cohort of PsA patients, a worsening in quality of life and work disability was observed. Disclosure of Interest: F. Colombres: None declared, H. Berman: None declared, A. Spindler: None declared, W. Spindler: None declared, J. Maldonado Cocco Grant/research support from: Pfizer Argentina, M. Orozco: None declared, E. Schneeberger Grant/research support from: Pfizer Argentina, A. Ortiz: None declared, S. Paira Grant/research support from: Pfizer Argentina, M. Zalazar: None declared, O. Rillo Grant/research support from: Pfizer Argentina, D. Baenas: None declared, A. Alvarellos Grant/research support from: Pfizer Argentina, T. Alvarellos: None declared, M. Garcia Grant/research support from: Pfizer Argentina, A. Salas: None declared, V. Duarte: None declared, F. Romanini Grant/research support from: Pfizer Argentina, L. Ferreyra Garrott: None declared, E. Soriano Grant/research support from: Pfizer Argentina, L. Galindo: None declared, G. Castelli: None declared, C. Borlenghi: None declared, A. Berman Grant/research support from: Pfizer Argentina